2016
DOI: 10.11113/jt.v78.8262
|View full text |Cite
|
Sign up to set email alerts
|

A Usability Evaluation of Mobile Application: A Review on Usability Model for the Deaf

Abstract: Usability is an important attribute that need more concentration in determining the production of a successful mobile application. Currently mobile applications for the deaf has increased tremendously with the increase of the usage of mobile phones. However, usability evaluation model that best suits the evaluation for mobile application for the deaf is rather very general. Usability of the mobile application for the deaf is very limited that makes the evaluation more challenging and difficult. This study revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…In the context of mobile learning, Nathan et al elaborated on a usability evaluation model applied to the design of mobile applications for DHH people. They suggested that future work should focus on establishing guidelines for the design of mobile applications for DHH education [23]. Furthermore, other researchers have argued that more research is needed in the area of online learning and the types of practices that make inclusion possible.…”
Section: Theoretical or Review/survey Studiesmentioning
confidence: 99%
“…In the context of mobile learning, Nathan et al elaborated on a usability evaluation model applied to the design of mobile applications for DHH people. They suggested that future work should focus on establishing guidelines for the design of mobile applications for DHH education [23]. Furthermore, other researchers have argued that more research is needed in the area of online learning and the types of practices that make inclusion possible.…”
Section: Theoretical or Review/survey Studiesmentioning
confidence: 99%
“…Usability commonly referred as a guideline for measuring usability of the system using models. These models provide insight into measurements to be used for usability analysis data collection [1]. Models such as International Standard Organization (ISO) 9241-11 [2] and Nielsen"s (2005) [3] model are among the common usability evaluation models that will be used in user evaluation to identify the issues [1].…”
Section: Introductionmentioning
confidence: 99%
“…These models provide insight into measurements to be used for usability analysis data collection [1]. Models such as International Standard Organization (ISO) 9241-11 [2] and Nielsen"s (2005) [3] model are among the common usability evaluation models that will be used in user evaluation to identify the issues [1]. However, when a specific targeted user application is developed, the user's requirement must be incorporated into the application.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations